UV/Vis+ photochemistry database: Structure, content and applications. (September 2020) - Noelle, Andreas; Vandaele, Ann Carine; Martin-Torres, Javier; Yuan, Chenyi; Rajasekhar, Balabhadrapatruni N.; Fahr, Askar; Hartmann, Gerd K.; Lary, David; Lee, Yuan-Pern; Limão-Vieira, Paulo; Locht, Robert; McNeill, Kristopher; et al.
Highlights: The "science-softCon UV/Vis + photochemistry database" contains EUV-VUV-UV–Vis-NIR spectral data. The database also contains quantum yields and photolysis related data. The database provides valuable information for astrophysics, earth and planetary sciences, medical and pharmaceutical sciences. Abstract: The "science-softCon UV/Vis + Photochemistry Database" (www.photochemistry.org ) is a large and comprehensive collection of EUV-VUV-UV–Vis-NIR spectral data and other photochemical information assembled from published peer-reviewed papers. The database contains photochemical data including absorption, fluorescence, photoelectron, and circular and linear dichroism spectra, as well as quantum yields and photolysis related data that are critically needed in many scientific disciplines. This manuscript gives an outline regarding the structure and content of the "science-softCon UV/Vis + Photochemistry Database". The accurate and reliable molecular level information provided in this database is fundamental in nature and helps in proceeding further to understand photon, electron and ion induced chemistry of molecules of interest not only in spectroscopy, astrochemistry, astrophysics, Earth and planetary sciences, environmental chemistry, plasma physics, combustion chemistry but also in applied fields such as medical diagnostics, pharmaceutical sciences, biochemistry, agriculture, and catalysis. In order to illustrate this, we illustrate the use of the UV/Vis + Photochemistry Database in four different fields of scientific endeavor.